Interaksi pengguna dalam persekitaran muzium maya (PMM) melalui pendekatan model berasakan imej - Normala Rahim
User interaction and interface design in the development of a virtual museum is an important element to meet the user requirement. Applications of existing virtual museums are not concerned with aspects of the real requirements, so the user can not interact easily, efficiently and effectively. The purpose of this study was to identify user requirement, user interaction techniques and interface design suitable for developing prototypes in the Virtual Museum Environment cYME). The methodology used to implement this research was User-Centered Design, which involves five phases, namely identify problems, initial analysis, design, development of prototype and evaluation. Preliminary analysis has produced a list of requirement through a questionnaire with 20 users that shows elements of user interaction which is navigation, manipulation and design interface must be incorporated in the prototype development. Thus, literacy studies carried out on user interaction and design techniques to realize the requirement of prototype development. Virtual Reality Panoramic (VRP) techniques that use is an approach Image Based Model is suitable for developing prototypes VME. VRP technique is carried out, there are two ways, namely inside-out views are used to navigate the environment and outside-in views are used to manipulate objects. The results of the analysis initial is a conceptual model of a virtual museum that helped design the environment of virtual museum which has features maps and hotspots to identify, plan and understand the location. These features help to build the study of mental map in the development of prototypes. To ensure that the prototypes meet the requirement of the usability evaluation conducted on 52 users to measure the satisfaction, efficiency, and easy to use. PMM have the highest fmding usability which is easy to use (Mean= 4.08), efficiency (Mean= 4.27) and satisfaction (Mean= 4.12). The main contribution of this study is the conceptual model and the interface design of pMM